Digital transformation of societies with the use of digital identity: a case study in Turkey - Sevgi Kavut (Obra Digital, 2024)
How digital identity and digital transformation will be able to affect societies has been a matter of wonder, particularly in the last decades. This study aims to reveal the importance of the digital transformation of societies, the use of digital identity, and digital citizenship degrees in Turkey. The study was carried out on adult individuals over 18 years old living in Istanbul, Ankara, and Izmir, the most significant three cities in terms of population and level of development in Turkey. As a result, this study shows that respondents' viewpoints differ in age, education levels,  and lived cities in the sub-dimensions of the Digital Identity Scale.